RETRACTED: Implementation of preventive corporate programs in education - Dolgova Valentina; Potapov Andrey; Kondratyeva Olga; Kapitanets Elena (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001